Pengaruh Digital Leadership Dan Creative Leadership Terhadap Inovasi Pelaku Usaha Kecil Dan Menengah Kota Malang - Sahputra, Ryan; Djaelani, Abdul Kodir; Slamet, Afi Rachmat (UNIVERSITAS ISLAM MALANG, 2025)
Abstract The Study Purpose now entering the digital era, where technology is no longer just a tool, but has become the main foundation in various economic, social and educational activities. Digital Leadership and Creative Leadership are relevant leadership approaches for MSME players, especially students in Malang City. The population in this study are students of Islamic University of Malang (UNISMA) who work in Small and Medium Enterprises (SMEs). The results showed that Digital Leadership and Creative Leadership have a positive and significant effect on the innovation of SMEs in Malang City, which means that the better the implementation of digital leadership and creative, the higher the level of innovation produced. Keywords: Digital Leadership, Creative Leadership, Small and Medium Enterprises (SMEs), Multiple Linear Regression